Distribution of Polycystine Radiolarians in Bottom Surface Sediments and Its Relation to Summer Sea Temperature in the High-Latitude North Atlantic - Matul, Alexander; Mohan, Rahul (Frontiers in Marine Science, 2017)
An objective of the study is to get new biogeographic information on the modern polycystine radiolarians from the high-latitude North Atlantic. The quantitative radiolarian dataset was compiled from publications and own micropaleontological counts from samples of the bottom surface sediments of the North Atlantic north of 40°N and Nordic Seas. Standard statistical treatment of micropaleontological data by factor analysis reveals five radiolarian assemblages which have their highest load at the specific temperature range in agreement with the oceanographic setting. An occurrence of radiolarian assemblages reflects extension and interaction of the warm North Atlantic and cold Polar/Arctic waters. Radiolarian distribution exhibits good correlation with the climatically averaged summer sea temperature on depth level of 200 m.